Combining Farrell Frontier and Hedonic Travel Cost Models for Valuing Estuarine Quality - Smith, V. Kerry; Palmquist, Raymond B.; Jakus, Paul (The Review of Economics and Statistics, 1991)
V. Kerry Smith, Raymond B. Palmquist, Paul Jakus, Combining Farrell Frontier and Hedonic Travel Cost Models for Valuing Estuarine Quality, The Review of Economics and Statistics, Vol. 73, No. 4 (Nov., 1991), pp. 694-699